National Geographic Magazine [computer file] The 1950s (vol. CXVI, no. 5, November 1959)1950-April 1953, May 1953-August 1956, September 1956-December 1959 (The Complete National Geographic Magazine : 110 year of National Geographic on CD-ROM, 1888)
Endure humanity's first cruel winter at the South Pole, as a team of scientists battles temperatures of 100 fahrenheit below zero. Explore the world's vast oceans with Captain Jacques-Yves Cousteau and his revolutionary Aqua-lung". Thrill to the conquest of Mount Everest in 1954. Discover the wreck of the Bountry and meet the direct descendants of Fletcher Christian and his crew. And experience many more captivating.